A global organism detection and monitoring system for non-native species - Graham, James J., author; Stolhgren, Thomas J., advisor; Laituri, Melinda J., advisor; Anderson, Charles W., committee member; Lefsky, M., committee member (Colorado State University. Libraries, 2006)
Invasive species are one of the greatest challenges to maintaining biodiversity and are a threat to human health. The Global Organism Detection and Monitoring system (GODM) has been created to allow users to: (1) manage invasive species research projects; (2) contribute data to a global invasive species dataset; (3) create maps of invasive species current and potential distributions; (4) perform analysis on datasets; and (5) extract and download data for further analysis and publication. This system can be accessed by anyone in the world with a connection to the Internet, a computer, and an Internet browser. GODM must integrate with an emerging cyberinfrastructure to take advantage of data and computing resources available on the Internet. To create GODM certain technical problems had to be solved including managing an unlimited amount of vector spatial data representing species occurrences. GODM represents a shift in how invasive species science is done, greatly increasing the pace of science based decisions with tools that are available to a much broader audience.
Keywords: environmental science